Efektivitas Pengelolaan Anggaran Dana Desa: (Studi Kasus Desa Borokanda Kecamatan Ende Utara Kabupaten Ende Propinsi NTT) - Damianus Tola; Jou Sewa Adrianus (Program Studi Pendidikan Ekonomi, Universitas Flores, 2020)
This research aims to know 1) the implementation of rural budgetary funds and 2) the effectiveness of the management of Borokonda’s rural fund in 2016 and 2018. The proponent factor on managing this rural fund is the high participation in managing and implementing the rural funds. Based on the effectiveness ratio, the management of rural funds in Borokonda from 2016 to 2018 is highly effective, with 99,98% stage of effectiveness. This is based on effectiveness ratio. This data is show as well that not every stage of effectiveness will be on 100% because there will always be a target which doesn’t realized optimally and it is also found that the rural fund which received by the government of Borokanda from 2016 to 2018 fluctuated, in which the received amount of rupiahs tends to change. Thus, the implementation of managing rural budgetary fund can be concluded as highly effective because it is consistent with the extent of society, appropriate, and effective as well.